Endoscopic palliation for inoperable malignant dysphagia: long term follow up. Issue 12 (December 1992) - Maunoury, V; Brunetaud, J M; Cochelard, D; Boniface, B; Cortot, A; Paris, J C
Abstract : This prospective non-randomised trial of 128 selected patients with unresectable oesophageal or gastrooesophageal junction cancers aims to evaluate the initial relief of malignant obstruction by means of bipolar electrocoagulation for both circumferential and submucosal strictures of Nd:YAG laser for the other patients. A limited dilatation was performed initially if a small calibre endoscope was unable to pass through the stricture. Prompt and significant relief of dysphagia without complications was achieved in 83% of patients. Improved patients were retreated monthly during the follow up period. Radiotherapy was recommended when possible. Symptomatic relief of obstruction lasted 4.2 months on average and 76% of patients remained palliated until death. Monthly retreatment using the most appropriate endoscopic procedure for the tumour configuration and radiotherapy after endoscopic relief of obstruction seems to give the best palliation for patients with unresectable cancers of the oesophagus or gastrooesophageal junction.